Pulmonary hypertension in patient with elevated homocystein level and blast injuries - Žuljević, Ervin (Array, 2009)
Abstract: 38-year-old man had chronic deep venous thrombosis (DVT) as a result of multiple injuries caused by an explosion of grenade 12 years ago, with recurrent pulmonary thromboembolisms and pulmonary hypertension which was unrecognized for a decade. Patient was admitted with a progressive dyspnea and exercise intolerance (NYHA II). The diagnosis was established according to clinical symptoms, transthoracic echocardiography, phlebography, lung scintigraphy and pulmonary angiography. Oral anticoagulant therapy was introduced and cava filter indicated to implant. During phlebography a floating thrombus was found in the inferior cava vein underneath renal vein. Implantation was delayed and patient received systemic fibrinolytic therapy with streptokinase (7 500 000 UI within 4 days), followed by heparin infusion and warfarin. Post-fibrinolytic phlebography showed clear lumen of inferior vena cava. Fibrinolysis had also affected pulmonary hypertension-systolic pressure in the right ventricle measured by Doppler echocardiography decreased from 90 to 65 mmHg. Permanent intravenous cava filter was implanted